Analisis Pengaruh Variabel Makroekonomi terhadap Return Saham Syariah Sektor Pertanian yang terdaftar di ISSI Periode 2011-2018 - Achmad Kharis; Imron Mawardi (Universitas Airlangga, 2019)
This study aims to determine the effect of GDP, Inflation, SBIS, Exchange Rates against Returns on Sharia Stocks in the Agriculture Sector Listed in the Indonesian Sharia Stock Index (ISSI). The approach used is quantitative by using the Vector Error Correction Model (VECM) analysis technique with the STATA program. While the GDP, Inflation, SBIS, Exchange Rates as independent variables and Returns on Sharia Stocks in the Agriculture Sector Listed in the Indonesian Sharia Stock Index (ISSI) as the dependent variable. The results of this study indicate that in the short term only GDP has a negative and significant effect. Whereas in the long run the GDP has a negative and significant effect, inflation has a positive and significant effect, SBIS has a negative and significant effect, Exchange rates have a positive and significant effect on the return of Agricultural Sector Sharia Shares registered at ISSI on the research period from 2011 to 2018.Keywords: GDP, Inflation, SBIS, Exchange Rates and Returns on Sharia Stocks in the Agriculture Sector Listed in ISSI